Fenomena Sosial Mahasiswa Jurusan Seni di Universitas Seni Tokyo Pada Anime Blue Period: Social Phenomenon of Art Students at Tokyo University of the Arts in Anime Blue Period - gilbran, issyaadhi; Arfianty, Rani (Undiksha Press, 2025)
This study explains the basics of sociology by detailing the views of figures such as Comte, Durkheim, and Weber. The anime